Indonesia Consumer’s Purchase Decisions and Private Label Brands: Study of Superindo Retailer - Saputri, Marheni Eka; Saraswati, Trisha Gilang (Universitas Muhammadiyah Surakarta, 2017)
Nowadays, private labeling has become a widely implemented strategy by modern market retailers. Retailers such as supermarkets and hypermarkets have superior supply chain in the country that they begin to extend their brand and make their own products, which is called private brand. The growth of private brands in Indonesia has been fairly stagnant as brand names step up both promotional activity and innovation efforts to protect share positions and drive growth. Based on Nielsen survey, the private label share in Indonesia only reaches one percentage. Why has the growth of private labelling in Indonesia been so slow? In short, Asian shoppers are strongly brand-loyal and retailers have not invested enough in marketing private label to persuade shoppers to trust its quality. Meanwhile, Superindo as one of the biggest retails in Indonesia has 8% growth of private brand share. Numerous studies have identified several factors affecting the purchase decision of private brand, and yet little empirical research has investigated the factors underlying consumer’s purchase decision of private brand in Indonesia especially of Superindo. In order to expand market share, private brands need to clearly identify what triggers consumer purchases. This paper aims to investigate the relationship between consumer’s decision-making styles and actual purchases of private label products in Indonesia market. This paper extends the work of Glynn and Chen (2009), Lian Fong et al (2015), and Thanasuta (2015) by examining Price consciousness, Price-quality association, Brand loyalty, Quality variability, Search vs. experience, Price perceived, Promotion, Brand Image, Quality Consciousness, Brand Consciousness, Value Consciousness, and Risk perception factors for investigation. In this research, both secondary data and primary were utilized. The primary data in the form of quantitative data were collected through online survey to 400 respondents and factor analysis was employed to identify the associations. The secondary data were obtained from relevant literatures, online journals, articles, blogs, and other electronic sources. The results indicate that Brand Consciousness and Search vs. experience influence consumer’s proneness to buy Private Brand.